Telemedicine Innovation for Stunting Education: Moving the Young Generation in Central Lampung - Syahroni, Arfan; Andriani, Silvia (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
Stunting is a condition in which a child's height falls below -2 standard deviations (SD) on the WHO growth curve, indicating that the child is short or very short. Indonesia's health development in the 2020-2024 period is focused on several priority programs, one of which is reducing stunting rates. One effort that can be made is increasing public knowledge about stunting prevention. This study aims to determine the effect of telemedicine based on a growth and development application on Android devices on improving the knowledge of adolescents in Central Lampung Regency. This research is a quantitative study using a cross-sectional study design. The sampling technique used was purposive sampling. The tools used in this study were an Android-based application and a questionnaire. Data analysis will be conducted using the non-parametric test (Wilcoxon). This study was conducted at SMA N 1 Sendang Agung with a sample of 54 respondents. The results of the study showed a significant effect of telemedicine (growth and development app) on improving adolescents' knowledge about stunting, with a p-value of 0.002 < 0.05. This indicates that the intervention through the app successfully improved adolescents' understanding of stunting. Increasing knowledge about stunting through the use of the growth and development app has proven effective. This app not only provides theoretical information about growth and development but also provides usable access, such as direct consultations with doctors. Therefore, recommendations can be given to expand the use of this app to more schools and other community groups to increase awareness and knowledge about stunting prevention widely.